CERITA POHON DESA”: DOKUMENTASI POHON PENEGAK SEBAGAI UPAYA PELESTARIAN LINGKUNGAN DAN BUDAYA LOKAL MELALUI KOLABORASI KAMPUNG BUDAYA PIJI WETAN DAN KKN UMKU 09 DESA LAU - Sukma Wijayanti; Saiful Ulya, Fera Afenia, Retno Dewi Setyowati, Divta Khoirun Nisa, Alin Wulandari, Kharisma Maulida (Adiba Aisha Amira, 2026)
Landmark trees play an important role not only as ecological supports, but also as part of the cultural identity of rural communities. The ‘Click, Village Tree Stories’ activity is the result of a collaboration between Kampung Budaya Piji Wetan and UMKU 09 Lau Village KKN students, which aims to document the existence of landmark trees through photography and reflective narratives. The methods used included field observations, object photography, information gathering from the community, and the compilation of tree descriptions. The result of this activity is a documentation book containing various types of landmark trees along with their ecological, social, and cultural stories. This activity demonstrates that visual documentation can be a medium for environmental education, strengthening community awareness, and a means of preserving local culture. It is hoped that this activity can be the first step in a sustainable effort to protect the village environment based on community participation.